A cross-sectional study evaluating health-related quality of life of Chinese pediatric patients with hematological malignancies using EQ-5D-Y - Sun, Yue; Zhou, Hui-Jun; Shen, Anle; Wu, Bin; Wang, Wei; Luo, Nan; Wang, Pei (Frontiers in Public Health, 2023)
Background The study aimed to assess health-related quality of life (HRQoL) and to estimate the health utility of pediatric patients with hematological malignancies (HMs) in China. Method A cross-sectional study recruited a series of pediatric inpatients diagnosed with HM from November 2018 to May 2019 in the Shanghai Children's Medical Center. Subjects were interviewed to collect sociodemographic information about themselves and their guardians. The EQ-5D-Y was completed by each patient to rate their own HRQoL, which later derived the health utility. The health status was also assessed by clinicians following the Eastern Cooperative Oncology Group (ECOG) system. Upon the descriptive analysis and univariate analysis, multivariate generalized linear models were built to explore the associations of risk factors with HRQoL measures of utility, Visual Analog Scale (VAS) score, and the five EQ-5D-Y domains. Results The 96 subjects had a mean age of 10.5 years and included 62 (64.4%) boys. There were 46 (47.9%) and 25 (26.0%) children diagnosed with acute lymphoblastic leukemia and non-Hodgkin's lymphoma, respectively. The means (SD) of utility and EQ-VAS scores were 0.88 (0.10) and 85.8 (15.1), respectively. Twenty-six (27.1%) patients were graded poor health by the ECOG standard (score 2/3). Both univariate and multivariate analyses found strong correlations between ECOG and HRQoL. After adjusting for covariates, poor ECOG score was significantly associated with an impaired utility and VAS of −0.103 and −8.65, respectively. With regard to individual HRQoL domains, worse ECOG was more likely to report health problems with an increased risk of 2.94 to 12.50; residence, income, guardians' education, and disease duration were also found to be significantly related to either the utility or certain health domains. Conclusion The HRQoL of Chinese pediatric patients with HM is considered relatively poor and of great concern to healthcare. With the strong correlations between EQ-5D-Y-related HRQoL measures and the traditional clinical index ECOG, the EQ-5D-Y is able to provide valuable evidence for clinical decision-making at the individual level. At the same time, its health utility can inform resource allocation at a macro level.